Lottery Rather than Waiting-Line Auction - KOH, Winston T. H. (Institutional Knowledge at Singapore Management University, 2006)
This paper investigates the allocative efficiency of two non-price allocation mechanisms – the lottery (random allocation) and the waiting-line auction (queue system) – for the cases where consumers possess identical time costs (the homogeneous case), and where time costs are correlated with time valuations (the heterogeneous case). We show that the relative efficiency of the two mechanisms depends critically on a scarcity factor (measured by the ratio of the number of objects available for allocation over the number of participants) and on the shape of the distribution of valuations. We show that the lottery dominates the waiting-line auction for a wide range of situations, and that while consumer heterogeneity may improve the relative allocative efficiency of the waiting-line auction, the ranking on relative efficiency is not reversed.